Integrated Health Services for Cancer Patients: an Urgent Need - Kusumawaty, Ira; Yunike, Yunike (International Journal Scientific and Professional, 2022)
Most cancer patients use a form of medication or complementary therapy. An integrative approach to cancer treatment is needed by combining conventional medicine and evidence-based complementary medicine/therapy and lifestyle interventions, for the treatment and prevention of disease and optimizing health through natural therapies by prioritizing community empowerment and local culture. The basis is a holistic approach; to treat the whole person as a whole, not just the disease. This utilizes additional technology that can assist the public in recognizing, detecting, undergoing diagnosis and monitoring the effectiveness of treatment. The purpose of this study was to identify the need for health services in cancer patients. The method used was a literature study by conducting studies on Scopus, Pubmed, and Google Scholar with the keywords cancer, health services.